2003
DOI: 10.1255/ejms.546
|View full text |Cite
|
Sign up to set email alerts
|

Charge Exchange in Tandem Mass Spectrometry: Dissociative Single Electron Capture by Doubly-Charged Toluene Cations

Abstract: Single electron capture by doubly-charged toluene cations upon collision with various target gases has been investigated by sector tandem mass spectrometry. Both non-dissociative and dissociative charge transfer reactions leading to C(7)H(7)(+) + H and to C(5)H(5)(+) + [C(2),H(3)] are detected. Seven atomic or molecular target gases have been used with ionisation energies ranging from 8.8 eV to 14 eV. The branching ratios between the different non-dissociative and dissociative exit channels have been determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…In low velocity charge transfer (CT) experiments, electronically excited states are also involved and responsible for the fragmentation [12]. In this low velocity domain (v ∼ 0.01 au), the role of the target ionization potential on the final internal energy of the cluster (or molecular ion) has been emphasized [13,14]. In high velocity collisions, where this work points, no detailed study of CT has been performed so far.…”
Section: Introductionmentioning
confidence: 99%
“…In low velocity charge transfer (CT) experiments, electronically excited states are also involved and responsible for the fragmentation [12]. In this low velocity domain (v ∼ 0.01 au), the role of the target ionization potential on the final internal energy of the cluster (or molecular ion) has been emphasized [13,14]. In high velocity collisions, where this work points, no detailed study of CT has been performed so far.…”
Section: Introductionmentioning
confidence: 99%
“…However, neither has the lifetime of the excited state been estimated so far nor does there exist direct experimental proof for the involvement of two electronic states in the near-threshold C 7 H 8 2+ ions. As to the structure of the toluene dication, early work of Meyerson has suggested that hydrogen atoms from the methyl group are about four times more probable to be lost than those coming from the ring, thus suggesting a “memory” of the toluene structure. Just like with the monocation surface, however, the interplay of TOL 2+ and CHT 2+ structures needs to be addressed carefully and moreover even other isomers need to be considered for the doubly charged species.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of such ions is oen revealed in time-of-ight (ToF) measurements by long "tails" on the corresponding ion ToF peaks, caused by the ions dissociating as they traverse the eld-free ight tube aer clearing the extraction region of the mass spectrometer. [35][36][37] A number of techniques have been used to study the unimolecular decay of multiply-charged ions, including tandem mass spectrometry, [38][39][40][41][42] photoelectronphotoion-photoion coincidence (PEPIPICO) [43][44][45][46][47] and covariance-map imaging. 31,36,[48][49][50][51] Covariance analysis of multimass velocity-map imaging datasets is a powerful technique which allows correlations between ions formed from the same individual molecule or cluster to be observed.…”
Section: Faraday Discussionmentioning
confidence: 99%
“…A number of techniques have been used to study the unimolecular decay of multiply-charged ions, including tandem mass spectrometry, 38–42 photoelectron–photoion–photoion coincidence (PEPIPICO) 43–47 and covariance-map imaging. 31,36,48–51 Covariance analysis of multimass velocity-map imaging datasets is a powerful technique which allows correlations between ions formed from the same individual molecule or cluster to be observed.…”
Section: Introductionmentioning
confidence: 99%